Minimum till lentil (Lens culinaris): an efficient way for rice fallow utilization and income enhancement in subtropical Tripura - YADAV, GULAB SINGH; DEVI, A GANGARANI; KANDPAL, BASANT; DAS, ANUP; BARMAN, K K; BABU, SUBHASH (The Indian Journal of Agricultural Sciences, 2020)
Lentil (Lens culinaris Medic.) can be a potential crop to intensify the rice (Oryza sativa L.) fallow land of Tripura to meet out the pulses requirement of the state. Thus, five lentil varieties, i.e. HUL-57, WBL-77, WBL-58, PL-06 and NDL-1 were demonstrated under three establishment methods, i.e. minimum till (MT), no-till (NT) and paira cropping (PC) on 75 farmers’ field at Moracherra, Dhalai, Tripura during winter seasons of 2012–14 in a participatory mode to gear up the pulse production in the state. Study revealed that the cultivation of lentil under MT and NT systems resulted in more number of branches/plant, pods/plant, seeds/pod and seed yield than those planted under PC. Hence, the farmers planted lentil under MT obtained more gross and net returns than those planted lentil under NT and PC. However, benefit to cost (B:C) ratio was significantly higher under PC than the other establishment methods. Lentil variety HUL-57 outperformed other varieties with respect to number of branches/plant, pods/plant, seeds/pod, seed yield and also recorded the highest gross and net returns and B:C ratio followed by WBL-77, WBL-58. Therefore, study recommended the cultivation of lentil varieties HUL-57, WBL-77 and WBL-58 under minimum tillage system for intensifying the rice fallows of Tripura to boost up the pulses production in the state.